The Assistance of Post-School Transition Program to Improve the Comprehension of The Academic Transition of Student with Special Needs for Inclusive School Teachers in Surakarta - Herry Widiyastono; Mahardika Supratiwi; Gunarhadi Gunarhadi; Hermawan Hermawan; Joko Yuwono; Dewi Sri Rejeki (Journal of Disability, 2022)
The post-school transition program prepares children with special needs (children with disabilities) for the transition from school to work, to the community, or to higher education at university. Children with disabilities have the least opportunity to get a job and continue their higher education because of their limitations. In addition, many teachers in inclusive schools need information about post-school transition programs, especially in the academic field. Therefore, it is necessary to provide assistance for teachers to obtain adequate information related to academic transition programs for children with disabilities in inclusive schools. This study aimed to provide mentoring on the post-school transition program to improve the understanding of the academic transition program for inclusive school teachers in Surakarta. This study used a one group pretest posttest design. The respondents of this study were 30 inclusive school teachers in Surakarta. The analysis technique used in this research is paired t-test analysis by comparing data before and after the implementation of mentoring. The results of the analysis showed that the value of t= -9.182 with p=0.0001 (p<0.05). These results indicate that there is a significant difference in the understanding of the post-school transition program in the academic field. Based on these results, it can be concluded that this mentoring program can improve respondents' understanding of the academic transition program material for children with disabilities.